Yet Another Victim of Kripkenstein’s Monster: Dispositions, Meaning, and Privilege - Andrea Guardo (Ergo, An Open Access Journal of Philosophy)
In metasemantics, semantic dispositionalism is the view that what makes it the case that, given the value of the relevant parameters, a certain linguistic expression refers to what it does are the speakers’ dispositions. In the literature, there is something like a consensus that the fate of dispositionalism hinges on the status of three arguments, first put forward by Saul Kripke—or at least usually ascribed to him. This paper discusses a different, and strangely neglected, anti-dispositionalist argument, which develops some remarks first put forward by Paul Boghossian and Anandi Hattiangadi and revolves around the idea that semantic dispositionalists have no way to justify their privileging certain dispositions, the ones they take to be reference-determining, over all the others. After some background (Section 1) and a first presentation of the argument (Section 2), I discuss three ways a dispositionalist might try to answer it and find them all wanting (Section 3).